[OP.3C.04] COMBINATION OF HEALTHY LIFESTYLE FACTORS ON THE RISK OF HYPERTENSION IN A LARGE COHORT OF HEALTHY ADULTS. (September 2017) - Lelong, H.; Kesse-guyot, E.; Galan, P.; Hercberg, S.; Blacher, J.
Abstract : Objective: Hypertension is the most prevalent chronic disease worldwide. Lifestyle behaviors for its prevention and control are widely recommended by guidelines. Nevertheless, little is known about their synergistic impact on hypertension, particularly in the general population. The aim of the present study was to compute a score of healthy lifestyle index (HLI) comprising the main non-pharmacological measures usually recommended to reduce the risk of hypertension: normal weight, physical activity, limited alcohol and salt consumption, and a healthy diet like the Dietary Approach to Stop Hypertension (DASH). Design and method: We prospectively examined the risk of hypertension among 80, 426 French adults participating in the NutriNet-Santé cohort study. Self-reported dietary, socio-demographic, lifestyle and health data were assessed at baseline and yearly using a dedicated website; the association between HLI and hypertension risk was assessed by multivariate Cox proportional hazards models adjusted for age, sex, body mass index, family history of hypertension, sociodemographic and lifestyle factors. Results: During a mean follow-up of 3.4 ± 2.1 years, 2, 413 incident cases of hypertension were documented. Compared with 0 or 1 healthy lifestyle factor, the hazard ratios for hypertension were HR: 0.76 (95% CI, 0.67–0.85) for 1 factor, 0.47 (95% CI, 0.42–0.53) for 2 factors, 0.35 (95% CI, 0.30–0.41) for all healthy lifestyle factors (P-trend < 0.0001). Compared with adhering to 0, 1, 2 or 3 healthy lifestyles, adhering to all them was found associated with a reduction of the hypertension risk of half (HR = 0.55 (95% CI, 0.46–0.65). Conclusions: In this large French cohort of healthy adults, adherence to healthy lifestyle factors was associated with a lower incidence of hypertension. In terms of public health, active promotion of healthy lifestyle factors at population level is key to combating the hypertension epidemic.